Evolution of catalyst coated atomised magnesium spheres: an alternative thermal storage medium for concentrated solar power applications - Mistry, Priyen C.; Grant, David M.; Stuart, Alastair D.; Manickam, Kandavel; Walker, Gavin S. (Elsevier, 2017)
Elevated temperature cycling studies were performed on two commercial gas atomised Mg spherical powders (average diameter of 26 μm and 30 μm) with magnetron sputtered catalysts (chromium, iron, vanadium and stainless steel) applied to their surfaces. At 350 °C, the presence of a catalyst promotes faster reaction kinetics with improving capacity until approaching stabilisation by the 90th cycle, e.g. the normalised capacity of V_Mg30 was found to rise from 45.5% to 65.5%. Following determination of activation energies (from Kissinger plots) and microstructural analysis of the post cycled structures a mechanism was proposed for the differing evolutions of the uncoated and coated Mg powders based upon a complex process in which particle sintering competes with particle fragmentation. Catalyst effectiveness varied with temperature, having a negligible impact on hydrogen storage characteristics of the atomised Mg powders following 50 cycles at 400 °C and this was mainly associated with the lack of multivalency in the catalysts.